Advancing ski tourism transformations to climate change: A multi-stakeholder participatory approach in diverse Canadian destinations - Natalie L.B. Knowles; Daniel Scott (Annals of Tourism Research Empirical Insights)
Canadian ski tourism destinations face increasing climate and carbon risks yet are not currently prepared to adapt to climate change or a decarbonized future. Considering the urgency of climate change and complexity of tourism systems, ski destinations need research identifying stakeholder-held climate and carbon risk perceptions, wider socioeconomic determinants of climate preparedness, and opportunities to accelerate climate decision-making and responsiveness. Using socioeconomic system frameworks, this study analyses secondary research including academic literature, climate action plans, alongside primary qualitative research collected from industry, government and community stakeholder narratives to investigate climate change and climate responsiveness in five Canadian ski tourism destinations. Despite localized climate and carbon risks, results highlight patterns impeding climate preparedness including rapid tourism growth, recreation resource corporatization, externalized climate action and sustainability, inequities, and lack of aspirational collective visioning. Conversely, stakeholders' pluralistic tourism and recreation values, sense-of-place, and interdependent relationships reveal pathways for mountain tourism destinations to transform towards climate resilient, sustainable, and just futures.